MAINTAINING A HEALTHY LIFESTYLE AND AVOIDING DIABETES FROM AN EARLY AGE - Adinda Rizkiah Nasution; Gishella Audia Sinaga; Jihan Fairuz; Hazel Raffif; Alfaridho Gandung Kurniwansyah (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2025)
This study aims to evaluate the risk factors for diabetes and identify preventive measures through a healthy lifestyle. Using epidemiological methods based on data from national surveys and literature studies, it was found that the prevalence of diabetes in Indonesia increased from 10.9% in 2018 to 11.7% in 2023. The results showed that poor diet, lack of physical activity, and obesity were the main factors. Implementation of a healthy diet, regular exercise, and regular health checks are recommended as preventive measures. These findings highlight the importance of public health education to reduce the prevalence of diabetes.